The Optimalization of Online Based Qur’an Teacher Training: SWOT Analysis for Improving the Quality of Education - Ningsih, Indah Wahyu; Heriyansyah, Heriyansyah; Kohar, Ade (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
The increasing demand for qualified Qur’an teachers in the digital era requires innovative training models that combine pedagogical quality with technological accessibility. The Tilawati Method, a widely used system for Qur’anic recitation instruction in Indonesia, has been adapted into an online format to meet this need. This study aims to optimize the implementation of online-based Qur’an Teacher Training using the Tilawati Method with a SWOT analysis approach to improve the quality of education. This study uses a qualitative method with data collection through interviews, observations, and documentation studies that are analyzed using a SWOT matrix. The results of the analysis show strengths such as time flexibility, cost efficiency, and detailed program structure; weaknesses such as dependence on internet connections and limitations of practice sessions; opportunities in equitable access to Qur’anic education; as well as threats in the form of infrastructure constraints and miscommunication between institutions. The proposed strategy includes technology optimization, improving post-training assistance services, and strengthening cooperation between central institutions and branches. This research is expected to be the basis for the development of Qur’an-based education policies based on the Tilawati Method that is continuous improvement.